Potret Moderasi dan Toleransi Beragama Dalam Tafsir Qs. al-Kafirun dan Relevansinya dalam Konteks Keindonesiaan - Muzakky, Althaf Husein (Al-Wasatiyah: Journal of Religious Moderation, 2022)
Tafsir Qs. Al-Kāfirūnis a form of religious dialogue between the Prophet and the Quraysh who upholds religious moderation. The word Al-Kāfirūnin its interpretation and Indonesian context is a sensitive issue in religious moderation. The ideal understanding of QS.Al-Kāfirūncan depict the portrait of the Prophet Muhammad's firm and wise tolerance. That the word infidel does not speak of people, but rather an attitude of infidel which can threaten religious moderation. This paper is presented through a qualitative method of thematic interpretation with thecontent analysis providing two conclusions. First, the principle of religious moderation is a cooperative task that is guarded as a social obligation of every religious believer. Second, religious moderation is a human effort to conceptualize a harmonious and prosperous life. The portrait of religious moderation according to the interpretation can be pursued through dialogue between religious adherents, mutual respect, tolerance and avoiding conflict. In the Indonesian context, tolerance and moderation can be strived through the Government of the Ministry of Religion, Local Culture, academics and scholars, Law in Indonesia.